Annual cotton/cowpea intercropping. I. Effect of row arrangement - de Azevedo, Demóstenes Marcos Pedrosa; Beltão, Napoleão Esberard de Macêdo; Vieira, Dirceu Justiniano; da Nóbrega, Laudemiro Baldoíno (Pesquisa Agropecuaria Brasileira, 1993)
A field experiment was carried out in Sousa, PB, Brazil (6o45'33"S and 18o13'56"W) with an "AW" climate according to Köppen, to investigate the effect of row arrangement in cotton (Gossypium hirsutum L.r. latifolium Hutch.) and cowpea (Vigna unguiculata L. Walp. subsp. unguiculata) intercropping. All row arrangement in intercropping showed yield advantages in relation to pure stands of individual crops. Double rows (2:2) were the only row arrangements which satisfied the condition of 75% of the sole cowpea (the most valuable crop) with the highest total LER value (1:30). The alternate rows (1:1) and 2 rows of cotton/1 row of cowpea (2:1) satisfied the minimum condition of 50% of the sole cowpea with LER values of 1.17 and 1.25 respectively. Three rows of cotton/1 row of cowpea did not satisfy the minimum cowpea yield requirement but obtained a considerably high LER value of 1.25. None of the treatments affected consistently the plant growth and fiber quality of cotton.